Association between air pollution exposure and coronary heart disease hospitalization in a humid sub-tropical region of China: A time-series study - Feng, Ya-Ting; Lang, Cui-Feng; Chen, Cong; Harry Asena, Musonye; Fang, Yang; Zhang, Ruo-Di; Jiang, Ling-Qiong; Fang, Xi; Chen, Yue; He, Yi-Sheng; Wang, Peng; Pan, Hai-Feng (Frontiers in Public Health, 2023)
Objective Emerging evidence has highlighted the possible links of environmental pollution with several cardiovascular diseases (CVDs). The current study aimed to explore the impact of short-term air pollution exposure on CHD hospitalization in Hefei. Methods Data about the daily number of CHD admissions (from 2014 to 2021) were retrieved from the First Affiliated Hospital of Anhui Medical University. Air pollutants and meteorological data were obtained from the China Environmental Monitoring Station and the China Meteorological Data Service Center, respectively. The correlation between air pollution and CHD hospitalization was assessed using distributed lag non-linear model (DLNM) and Poisson generalized linear regression. Results In the single-pollutant model, NO2, O3, and CO strongly correlated with CHD hospitalization rate. Specifically, exposure to NO2 (lag0, relative risk [RR]: 1.013, 95%CI: 1.002–1.024, per 10 μg/m3 increase) and CO (lag13, RR: 1.035, 95%CI: 1.001–1.071, per 1 μg/m3 increase) revealed a positive correlation with an increased rate of CHD hospitalization. Interestingly, O3 had a protective association with hospitalization of CHD (lag0, RR: 0.993, 95%CI: 0.988–0.999, per 10 μg/m3 increase). Similar results, to those of the single-pollutant model, were revealed following verification using two-pollutant models. Subgroup analyses indicated that young people, women, and people in hot seasons were more susceptible to NO2 exposure, while the elderly, women, and people in cold seasons were more susceptible to O3. Furthermore, the elderly were more susceptible to CO exposure. Conclusion Overall, exposure to NO2 and CO increases the rate of CHD hospitalization, but exposure to O3 shows a protective association with the rate of CHD hospitalization. Therefore, early preventive measures against air pollutants should be applied to protect vulnerable patients with CHD.